An Easy and Rapid Transformation Protocol for Transient Expression in Cotton Fiber - Shang, Xiaoguang; Zhu, Lijie; Duan, Yujia; He, Qingfei; Zhao, Meiyue; Yu, Yujia; Guo, Wangzhen (Frontiers in Plant Science, 2022)
Cotton fiber is the most important natural textile material in the world. Identification and functional characterization of genes regulating fiber development is fundamental for improving fiber quality and yield. However, stable cotton transformation is time-consuming, low efficient and technical complex. Moreover, heterologous system such as Arabidopsis and tobacco did not always work to elucidate the function of cotton fiber specifically expressed genes or their promoters. For these reasons, constructing a rapid transformation system using cotton fibers is necessary to study on fiber specifically expressed genes. Here, we developed an easy and rapid Agrobacterium-mediated method for transient transformation of genes and promoters in cotton fibers. First, we found that exogenous genes could be expressed in cotton fibers via using β‑glucuronidase (GUS) and green fluorescence protein (GFP) as reporters. Then, parameters affecting transformation efficiency, including LBA4404 Agrobacterium strain, 3 h infection time and 2 d incubation time were determined. Third, four different cotton genes that are specifically expressed in fibers were transiently transformed in cotton fibers, and the transcripts of these genes were detected ten to thousand times increase over the control. Fourth, GUS staining and activity analysis demonstrated that the activity profiles of GhMYB212 and GhFSN1 promoters in transformed fibers are similar to its native activity in developmental fibers. Furthermore, the transient transformation method was confirmed to be suitable for subcellular localization studies. In summary, the presented Agrobacterium-mediated transient transformation method is a fast, simple and effective system for promoter characterization and protein expression in cotton fibers.